FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP CEMARAN AIR MINUM ISI ULANG OLEH ESCHERICHIA COLI DI KOTA DENPASAR TAHUN 2015 - Sabariah Sabariah (JURNAL KEDOKTERAN, 2018)
Drinking water is water that meets quality of health. The requirements include microbiology, chemistry, physics and radioactivity aspects.The high public interest in the consumption of bottled water and high prices of bottled drinking water encourage. However, the growth of refill drinking water (AMIU), licensing, training, supervision and circulation can not be done properly, which affect the poor drinking water quality assurance that could potentially cause harm to health.The study was a analytical descriptive study with cross sectional. This study showed 7 (15.6%) of 45 refilled drinking water were contaminated with E.coli. The factors that were not related with E.coli contamination were raw water (p = 0.181> 0.05), the disinfectant (p = 0.368) and sanitary facilities (p=0.771). However, it was related with sanitary location (p=0.000).Factors associated with E.coli contamination in drinking water refilled depot in Denpasar city.